Involvement of CYP2E1 in the Course of Brain Edema Induced by Subacute Poisoning With 1,2-Dichloroethane in Mice - Jin, Xiaoxia; Liao, Yingjun; Tan, Xiaoqiong; Wang, Gaoyang; Zhao, Fenghong; Jin, Yaping (Frontiers in Pharmacology, 2018)
This study was designed to explore the role of cytochrome P4502E1 (CYP2E1) expression in the course of brain edema induced by subacute poisoning with 1,2-dichloroethane (1,2-DCE). Mice were randomly divided into five groups: the control group, the 1,2-DCE poisoned group, and the low-, medium- and high-dose diallyl sulfide (DAS) intervention groups. The present study found that CYP2E1 expression levels in the brains of the 1,2-DCE-poisoned group were upregulated transcriptionally; in contrast, the levels were suppressed by DAS pretreatment in the intervention groups. In addition, the expression levels of both Nrf2 and HO-1 were also upregulated transcriptionally in the brains of the 1,2-DCE-poisoned group, while they were suppressed dose-dependently in the intervention groups. Moreover, compared with the control group, MDA levels and water contents in the brains of the 1,2-DCE-poisoned group increased, whereas NPSH levels and tight junction (TJ) protein levels decreased significantly. Conversely, compared with the 1,2-DCE- poisoned group, MDA levels and water contents in the brains of the intervention groups decreased, and NPSH levels and TJ protein levels increased significantly. Furthermore, pathological changes of brain edema observed in the 1,2-DCE-poisoned group were markedly improved in the intervention groups. Collectively, our results suggested that CYP2E1 expression could be transcriptionally upregulated in 1,2-DCE-poisoned mice, which might enhance 1,2-DCE metabolism in vivo, and induce oxidative damage and TJ disruption in the brain, ultimately leading to brain edema.